The Dilemma of Indonesia Welfare State Challenge of Realizing Social Welfare in the Global Era - Hs. Tisnanta; James Reinaldo; Fathoni Fathoni (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
Globalization has placed Indonesia in a dilemma in creating the welfare of the people. Many legislations with liberal character are disallowed through the constitutional review by the constitutional court. The liberal character then becomes constraints for government to realize social welfare, thus harming the economic interest of people and contrary to the constitution (UUD 1945). Efforts to create welfare cannot be separated from state sovereignty in determining the economics welfare policy in the form of law. The State needs to adopt policies of recalibrating sovereignty to realize its objectives. Sovereignty is the essential requirement to be able to build pengayoman law character, ideology by Pancasila ideology and UUDNRI 1945. The legal substance of pengayoman law (protection and succor) will realize a balance between global interests and the interests of the nation. Pengayoman Law integrates the efficiency and freedom with fairness and welfare excellence. Also, the Pengayoman Law always opens the space to give a guarantee/partiality to the poor through social policies that are based on human dignity. Keywords: Welfare, Challenges, Globalization, Dilemma